Magnesium-Sodium Hybrid Battery With High Voltage, Capacity and Cyclability - Zhang, Ruigang; Tutusaus, Oscar; Mohtadi, Rana; Ling, Chen (Frontiers in Chemistry, 2018)
Rechargeable magnesium battery has been widely considered as a potential alternative to current Li-ion technology. However, the lack of appropriate cathode with high-energy density and good sustainability hinders the realization of competitive magnesium cells. Recently, a new concept of hybrid battery coupling metal magnesium anode with a cathode undergoing the electrochemical cycling of a secondary ion has received increased attention. Mg-Na hybrid battery, for example, utilizes the dendritic-free deposition of magnesium at the anode and fast Na+-intercalation at the cathode to reversibly store and harvest energy. In the current work, the principles that take the full advantage of metal Mg anode and Na-battery cathode to construct high-performance Mg-Na hybrid battery are described. By rationally applying such design principle, we constructed a Mg-NaCrO2 hybrid battery using metal Mg anode, NaCrO2 cathode and a mixture of all-phenyl complex (PhMgCl-AlCl3, Mg-APC) and sodium carba-closo-dodecaborate (NaCB11H12) as dual-salt electrolyte. The Mg-NaCrO2 cell delivered an energy density of 183 Wh kg−1 at the voltage of 2.3 V averaged in 50 cycles. We found that the amount of electrolyte can be reduced by using solid MgCl2 as additional magnesium reservoir while maintaining comparable electrochemical performance. A hypothetical MgCl2-NaCrO2 hybrid battery is therefore proposed with energy density estimated to be 215 Wh kg−1 and the output voltage over 2 V.